DNA nanostructures from double-C-shaped motifs with controllable twist and curvature. Issue 31 (26th July 2019) - Yang, Donglei; Huang, Kai; Wang, Pengfei; Mi, Yongli; Wei, Bryan
Abstract : We demonstrate twist and curvature engineering in DNA nanostructures from the scaffold-free approach. Abstract : We demonstrate twist and curvature engineering in DNA nanostructures from the scaffold-free approach. The DNA 'LEGO' bricks adopted in this study are double-C-shaped motifs, and extended nanostructures are constructed to visualize the structural details of twist or curvature. By systematically deleting and inserting base pairs at certain domains of the component motifs, we are able to study various levels of the twist and curvature of the resulting nanostructures comprehensively.